Sedimentological sand grain orientation in oil-producing U1 layer Kazan oil-gas-condensate field (Tomsk Oblast); IOP Conference Series: Earth and Environmental Science; Vol. 33 : Contemporary Issues of Hydrogeology, Engineering Geology and Hydrogeoecology in Eurasia - Krasnoshchekova L. A. Lubov Afanasievna (Geology, Hydrogeology and Engineering Geology, 2016)
Title screen